2020
DOI: 10.3390/ijms21062008
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Autophagy and Autophagy Receptor NDP52 in Microbial Infections

Abstract: Autophagy is a general protective mechanism for maintaining homeostasis in eukaryotic cells, regulating cellular metabolism, and promoting cell survival by degrading and recycling cellular components under stress conditions. The degradation pathway that is mediated by autophagy receptors is called selective autophagy, also named as xenophagy. Autophagy receptor NDP52 acts as a ‘bridge’ between autophagy and the ubiquitin-proteasome system, and it also plays an important role in the process of selective autopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 99 publications
(110 reference statements)
0
15
0
Order By: Relevance
“…Human NDP52 consists of the SKIP carboxyl homology (SKICH), LC3-interacting region (LIR), coiled-coil, galectin-8 binding (GALBI), and C-terminal ubiquitin-binding zinc finger (UBZ) domains ( 17 , 19 ) ( Figure 1A ). The substitution of Asp439 by Arg (D439R) in the UBZ domain reportedly abolishes the ubiquitin-binding ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human NDP52 consists of the SKIP carboxyl homology (SKICH), LC3-interacting region (LIR), coiled-coil, galectin-8 binding (GALBI), and C-terminal ubiquitin-binding zinc finger (UBZ) domains ( 17 , 19 ) ( Figure 1A ). The substitution of Asp439 by Arg (D439R) in the UBZ domain reportedly abolishes the ubiquitin-binding ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…NDP52 is a multifunctional regulatory protein that predominantly works in selective autophagy ( 17 , 18 ). Although linear (de)ubiquitination is involved in the NDP52-mediated xenophagy of invading Salmonella ( 24 , 25 ), little is known about the crosstalk between NDP52 and LUBAC in innate immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to binding myosin VI, T6BP/TAX1BP1 and CALCOCO2/NDP52 also bind each other and have been suggested to modulate cytokine signaling and membrane transport with actin filament organization and cell adhesion [ 47 ]. There are several recent studies on CALCOCO2/NDP52 that have revealed important molecular insights on its role as the recruiter of the early autophagic protein complexes to the cargo, initiating selective autophagy [ 48 50 ], and a recent review summarizes its role in microbial infections, including viruses [ 51 ]. CALCOCO2/NDP52 has a role in innate immunity through NFKB and type I IFN regulation, which can be another explanation for CSFV CALCOCO2/NDP52 targeting.…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 40 , 41 A previous report has shown that NDP52, an autophagy receptor, links autophagy and the UPS. 42 Rapamycin-induced autophagy promotes cell survival in the presence of proteasome inhibitors in vivo and in vitro. 43 , 44 Proteasome inhibition activates autophagy, with p62 acting as a bridge.…”
Section: Discussionmentioning
confidence: 99%